An analysis of the physical demands of Division I collegiate womens soccer with positional considerations - Corrales, I.; Coburn, J.; Lynn, S.; Lockie, R. (The Journal of Strength and Conditioning Research, 2021)
Introduction: Soccer is a demanding sport in which players need to be technically, tactically, and physically skilled. Match performance can be influenced by competition level and player position. For example, elite midfielders tend to cover more total distance and complete more high-intensity efforts than forwards and defenders. Although match demands for collegiate female soccer players could be similar, there is limited research describing the competition demands and between-position differences at this level. Purpose: To determine the demands of Division I collegiate women's soccer and any between-position differences. Methods: A convenience sample of 10 NCAA Division I soccer players (3 forwards, 3 midfielders, 4 defenders) from the same team were analyzed. Goalkeepers were excluded due to different movement demands. Data was collected during typical monitoring practices for the team from each player across 8 matches using GPS technology, which had a sampling rate of 10 Hz. The analyzed metrics from the proprietary software included: total distance (TD); total sprint distance (TSD; a sprint was defined as traveling above 4.75 m/s for at least 1 second, ending when speed drops below 3 m/s); number of sprints (NS); explosive efforts (EE; acceleration to at least 4.75 m/s from below 2.2 m/s, sustained for at least 1.5 seconds); top speed (TS); and GPS load (GPSLoad; value accounting for intensity and duration of movements in different speed zones; measured in arbitrary units [AU]). A one-way ANOVA (p < 0.05) and effect sizes (d) calculated any between-position differences. Results: No significant differences were found between positions for any variable, although there were large-to-very large effects for many comparisons. Midfielders covered the greatest TD (~9,116.73 m) compared to forwards (~8,359.46 m; d = 1.99) and defenders (~7,694.62 m; d = 2.33). Forwards had the greatest high-intensity work shown by TSD, NS, and EE (~938.01 m, ~42, and ~35) compared to midfielders (~753.84 m, ~34, and ~28; d = 1.99-2.00) and defenders (~600.35 m, ~25, and ~23; d = 2.25-2.29). Forwards had the highest TS (~17.31 km/h-1) compared to defenders (~16.85 km/h-1; d = 1.91) and midfielders (~16.08 km/h-1; d = 1.80). GPSLoad was highest for forwards (~193.35 AU), compared to midfielders (~182.62 AU; d = 1.95) and defenders (~149.11 AU; d = 2.32). Conclusions: The ANOVA data seemed to suggest limited between-position differences in the variables. This may have been influenced by the sample size, and substitutions were not considered. However, the effect size data showed some clear between-position differences, such as, midfielders covering the greatest TD. Forwards completed the highest TSD, NS, and EE, which may be related to their need to make space to receive the ball. It should be noted that these movement characteristics are important across all positions to create attacking opportunities. TS and GPSLoad was relatively similar across positions, which may be a function of the team training (players developed similar TS) and tactics (coaches limited player work and thus GPSLoad). Practical Applications: Attention may be applied to midfielders in developing their speed and aerobic capacity. This may be beneficial in improving defensive performance when pressing opposition ball-carriers, or when creating goal opportunities. Strength coaches could emphasize speed development in forwards and defenders to potentially create or prevent more goal scoring opportunities.